2007
DOI: 10.1021/jp066710u
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Order Properties in Fluorinated Liquid Crystals from an Optical, Dielectric, and 13C NMR Combined Approach

Abstract: Orientational order properties of two fluorinated nematogens, exhibiting a wide nematic range, have been investigated by means of optical methods, dielectric spectroscopy, and 13C NMR. 13C NMR spectra have been recorded by 1H-SPINAL decoupling CP techniques under both static and magic angle spinning conditions. The order parameters of the fluorinated aromatic fragments have been calculated by analyzing the 13C−19F dipolar couplings at different levels of approximations by means of a least-squares fitting proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 43 publications
5
48
0
Order By: Relevance
“…According to the Maier and Meier equations (15), the dielectric anisotropy is proportional to the order parameter divided by temperature: Á" , S(T)/T (other factors are only slightly dependent upon T). It has been shown that the S-values obtained in this way agree well with those determined by the nuclear magnetic resonance (NMR) and optical anisotropy methods (16,17). The order parameters calculated in this way are presented in Figure 9.…”
supporting
confidence: 69%
“…According to the Maier and Meier equations (15), the dielectric anisotropy is proportional to the order parameter divided by temperature: Á" , S(T)/T (other factors are only slightly dependent upon T). It has been shown that the S-values obtained in this way agree well with those determined by the nuclear magnetic resonance (NMR) and optical anisotropy methods (16,17). The order parameters calculated in this way are presented in Figure 9.…”
supporting
confidence: 69%
“…(c) Evolution of the aromatic region of the proton‐decoupled 13 C CP NMR static spectrum of 3CyCyBF2 with temperature in the N phase. Adapted from and .…”
Section: Applicationsmentioning
confidence: 99%
“…Fluorinated nematogens containing mono‐fluorinated or di‐fluorinated phenyl rings and cyclohexane in the core, structurally resembling those studied by Magnuson et al ., were more recently investigated by Catalano et al . (3CyHeBF and 3CyCyBF2 in Table , with 3CyCyBF2 corresponding to 3CCP F F of ) and Geppi et al .…”
Section: Applicationsmentioning
confidence: 99%
“…The permittivity values of 3CyHeBF are considerably lower than those measured for other substances. This is due to smaller value of the dipole moment (,2.1 D for 3CyHeBF, ,3.0 D for three other compounds (6,7)). For 3CyCyBF2 and 3Cy2CyBF2 the permittivity values are practically the same in spite of the presence of the CH 2 CH 2 bridging group in the latter case.…”
Section: Discussionmentioning
confidence: 96%
“…Below the nematic-SmB phase transition, the 5CyCy2BF2 sample could not be aligned and the permittivity dropped considerably. The dielectric anisotropy of these compounds in their nematic phase, De5e I 2e ) , was recently analysed in terms of the order parameter, together with the results obtained by 13 C NMR and optical methods (6,7). In this paper, attention will be focused on the dynamic properties of molecules in different phases.…”
Section: Methodsmentioning
confidence: 99%